ANALISIS PERAMALAN JUMLAH PRODUKSI HIJAB MENGGUNAKAN METODE FORECASTING (Studi Kasus Pada Aliya Hijab Collection Kabupaten Tasikmalaya) - Tetin Adawiah; Suci Putri Lestari; Kusuma Agdhi Rahwana (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine and predict the optimal amount of production the must be carried out by the company by predicting the data on the amount of production owned by the Aliya Hijab Collection for the period January to December 2021. The data collection method ini this study was by direct observation on the Aliya Hijab Collection, using interview techniques, observation and documentation. The Analytical tools used are forecasting method such as moving average and exponential smoothing. The results of the forecasting analysis show that the 3- month moving average method is better for companies because the forecasting error is smaller. The company should follow the calculation of the 3-month moving average forecasting method so as to be able to predict and determine the optimal amount of production.